THE USE OF GRAMMARLY TOOLS TO ENRICH STUDENT'S WRITING ABILITY - Putri Maulidina; Hanafi Wibowo (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2022)
This research was carried out to know how the students’ activities in learning using Grammarly in improving students writing skills. Thirty-three students from class X DKV-E of SMK Bakti Mandiri participated in this study. This research is being conducted in two cycles using a Classroom Action research Approach. Using the Arikunto model, this study was carried out using the action research strategies of planning, acting, observing, and reflecting. In this study, information was acquired through interviews, observations, questionnaires, and tests. The writer then analyzed the data, both quantitative and qualitative. The conclusion of the study demonstrated that there was an improvement in students’ writing abilities. The majority of students gradually improved their results at the conclusion of each cycle. The English lesson's Minimum Mastery Criterion (KKM) score was 78. The preliminary study's mean score for the students was 76.10, and the percentage was 45%. In the first cycle, the students' mean score was 77.10 while the percentage was 57%. In the second cycle, the mean score was 80.68, and the percentage was 84%. Moreover, there was a positive response from the English teacher about implementing the action. In summary, Grammarly can improve students’ writing ability.